DAYA TARIK PANTAI BALANGAN JIMBARAN BALI MENURUT WISATAWAN NUSANTARA MILENIAL - Adita Nadi Christy Telly Kaunang; I Gusti Bagus Rai Utama (Bajang Institute, 2022)
This study, it is discussed the factors that are considered by domestic millennial tourists to choose Balangan Beach as a tourist attraction. There are two objectives in this research. The first is to determine what factors are taken into consideration by Millennial Tourists choosing Balangan Beach as a Tourist Attraction. The second is to determine the dominant factors for Millennial Tourists choosing Balangan Beach as a Tourist Attraction. This research was conducted with 70 respondents. The analysis technique used factor analysis consisting of variable selection, factoring process, naming each factor, and model determination test. This study resulted in three factors, namely flora and fauna factors, field availability, and information center factors which are factors that influence millennial tourists to choose Balangan Beach as a place to do tourism. At the same time, the most dominant factor is the information center factor which has the greatest eigenvalue.